The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5039/agraria.v12i4a5474
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of X-ray test to evaluate the physiological quality of sesame seeds due to fruits position at the plant

Abstract: The IAC-Ouro sesame cultivar has recently expanded to Brazilian Northeast, but the studies related to physiological quality and vigor of seeds produced under these conditions are scarce yet. Due to difference in fruits maturity from different parts of the plant, the aim of this study was to relate X-ray images with the seed maturation degree and evaluate the quality of seeds from fruits located on the lower, middle and upper third of the stem. We growth the sesame in an experimental area and harvest the fruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Other factors related to seed constitution may also affect the detailing of internal structures on the radiograph that is generated (Arruda et al, 2016). Nogueira Filho et al (2017) observed that the X-ray test did not allow determination of the level of development of the internal structures of sesame seeds, due to the impossibility of visualizing these structures, which resulted from the high oil concentration in sesame seeds, typical of oilseed plants. In this respect, the low oil concentration in L. leucocephala seeds, around 5.44% (Nehdi et al, 2014), may have contributed to allow visualization of the internal structures of the seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors related to seed constitution may also affect the detailing of internal structures on the radiograph that is generated (Arruda et al, 2016). Nogueira Filho et al (2017) observed that the X-ray test did not allow determination of the level of development of the internal structures of sesame seeds, due to the impossibility of visualizing these structures, which resulted from the high oil concentration in sesame seeds, typical of oilseed plants. In this respect, the low oil concentration in L. leucocephala seeds, around 5.44% (Nehdi et al, 2014), may have contributed to allow visualization of the internal structures of the seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the water content, the level of detail of the internal seed parts of the radiographic image can be affected by other intrinsic factors of each species, such as its chemical composition (Simak, 1991). In sesame seeds, the X-ray test did not allow the determination of the level of development of internal seed structure, which according to the authors was due to its high oil content, typical of oilseeds (Nogueira-Filho et al, 2017). However, as shown in Figure 1, in melon seeds, whose oil content is within the range of 25.2 to 44.8% (Ibeto et al, 2012), it was possible the visualization with a high degree of detail of the internal seed morphology, with easy visual identification of seeds with incomplete filling and embryonic malformation ( Figure 1B), as well as physical damage caused by predation of insects and cracks, possibly during handling or drying processes ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Relative and integrated density are variables used recently in research with seeds, which are still little reported, but with great potential for evaluating seed lots (ABUD; CICERO; MEDEIROS et al, 2018). These variables, calculated using the gray values of each pixel in the image, off er an idea of the resistance that a given tissue has to the passage of X-ray waves since the photons in an X-ray beam can be transmitted, scattered (Compton eff ect) or absorbed (photoelectric collision) when they collide with an object (KOTWALIWALE et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This method has proven effi cacy to determine the internal morphology and parameters associated with the physiological quality of several plant species, such as Cucumis sativus L. (GOMES JUNIOR; CHIQUITO; MARCOS FILHO, 2013), Cucurbita pepo L. (ANTONIO et al, 2016;SILVA et al, 2014), Solanum aethiopicum L. (ALVES et al, 2018), Brassica oleracea L. var. italica (ABUD; CICERO; GOMES JUNIOR, 2018), Helianthus annuus L. (ROCHA; SILVA; CICERO, 2014), Crotalaria juncea L. (ARRUDA; CICERO; GOMES JUNIOR, 2016), Sesamum indicum L. (NOGUEIRA FILHO et al, 2017), Acca sellowiana (SILVA et al, 2013), Swingle citrumelo (ARRUDA; CICERO; GOMES JUNIOR, 2018), Anacardium occidentale L. (SILVA et al, 2017), Brachiaria brizantha. (JEROMINI et al, 2019), Terminalia argentea (GOMES et al, 2014), among other species.…”
Section: Introductionmentioning
confidence: 99%